Functional and mechanistic characterization of an atypical flavin reductase encoded by the pden_5119 gene in Paracoccus denitrificans - Sedláček, Vojtěch; Kučera, Igor (Molecular microbiology, 2019)
Pden_5119, annotated as an NADPH-dependent FMN reductase, shows homology to proteins assisting in utilization of alkanesulfonates in other bacteria. Here, we report that inactivation of the pden_5119 gene increased susceptibility to oxidative stress, decreased growth rate and increased growth yield; growth on lower alkanesulfonates as sulfur sources was not specifically influenced. Pden_5119 transcript rose in response to oxidative stressors, respiratory chain inhibitors and terminal oxidase downregulation. Kinetic analysis of a fusion protein suggested a sequential mechanism in which FMN binds first, followed by NADH. The affinity of flavin toward the protein decreased only slightly upon reduction. The observed strong viscosity dependence of kcat demonstrated that reduced FMN formed tends to remain bound to the enzyme where it can be re-oxidized by oxygen or, less efficiently, by various artificial electron acceptors. Stopped flow data were consistent with the enzyme-FMN complex being a functional oxidase that conducts the reduction of oxygen by NADH. Hydrogen peroxide was identified as the main product. As shown by isotope effects, hydride transfer occurs from the pro-S C4 position of the nicotinamide ring and partially limits the overall turnover rate. Collectively, our results point to a role for the Pden_5119 protein in maintaining the cellular redox state.
Keywords: Flavin-Adenine Dinucleotide; Paracoccus denitrificans; NADPH-cytochrom c-reduktasa; oxidace-redukce; FMN Reductase; flavinadenindinukleotid; flaviny; NADPH-Ferrihemoprotein Reductase; Amino Acid Sequence; flavinmononukleotid; transport elektronů; Oxidation-Reduction; NADP; Flavin Mononucleotide; FMN-reduktasa; terciární struktura proteinů; Electron Transport; Protein Structure, Tertiary; Flavins; sekvence aminokyselin